New Tool to Screen Financial Viability of Alternative Public–Private Partnership Structures for Delivery of Electric Vehicle-Charging Infrastructure - Patrick DeCorla-Souza; Mahir Hossain (World Electric Vehicle Journal)
This paper demonstrates the use of an Excel-based tool called the “Electric Vehicle-Charging Infrastructure Financial Analysis Spreadsheet Tool”, or “EVCI-FAST”, developed to analyze public–private partnership approaches to deliver publicly accessible EV-charging infrastructure that would not be commercially viable without a government subsidy. To demonstrate the use of this tool, we conducted a high-level screening analysis for a hypothetical bundle of publicly accessible EV-charging stations to assess the financial viability of delivering electric vehicle-charging infrastructure (EVCI) using alternative public–private partnership (P3) structures. This demonstration suggests that the EVCI-FAST could assist public agencies in determining whether their budgetary resources are adequate to support a proposed P3 for an EVCI project. The demonstration suggests that the EVCI-FAST could also help agencies decide which P3 structuring option would best meet their financial objectives. The results from the analysis of the hypothetical project suggest that public agencies could benefit considerably from a P3 structure that uses a minimum revenue guarantee to reduce revenue risk for the private partner.